Pengembangan Buku Nonteks Berbasis Riset Karakterisasi Salak Padangsidimpuan (Salacca Sumatrana Becc.) - Rahma, Aisyah; Hasairin, Ashar; Idramsa, Idramsa (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to produce a non-textbook product about the development of a non-textbook based on research into the characterization of Salak Padangsidimpuan (Salacca Sumatrana Becc.). This study uses research and development (R&D) methods with the 4D Thiagarajan development model, which includes the stages of definition, design, development, and dissemination. The results of the study indicate that product validation by content experts obtained a score of 89.1%, categorized as "very feasible." Language experts gave a score of 81%, also categorized as "very feasible," while learning design experts assessed the product with a score of 92.3%, falling into the same category. Feedback from biology lecturers showed that the book is suitable for use, with an average score of 88.9%, classified as "very feasible." In user trials, individual trials resulted in a score of 81.9%, small group trials 82.6%, and limited group trials reached 82.2%, all in the "very feasible category”. In conclusion, the developed non-textbook is highly suitable for use as a reference in teaching spermatophyte taxonomy for biology students. Keywords: Non-textbook, Padangsidimpuan, Development, Salacca Sumatrana